2012
DOI: 10.1088/0253-6102/57/5/19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Higher Order Axial Electron Temperature on Self-Focusing of Electromagnetic Pulsed Beam in Collisional Plasma

Abstract: Effect of higher order axial electron temperature on self-focusing of electromagnetic pulsed beam in collisional plasma is investigated. It is shown that higher order axial electron temperature Tp4 is not trivial than Tp0 and Tp2, which can modify slightly radial redistribution of electron density and increases effective dielectric constant. As a result, on one hand, slightly reduce electromagnetic beam self-focusing in the course of oscillatory convergence, on the other hand, quicken beam divergence in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It changes the electron density distribution and increases the dielectric constant therefore, leads to fast divergence of the laser beam. [23] Sprangle et al [24] investigated the relativistic self-focusing of short-pulse radiation beams in plasmas and reported that for self-focusing to occur, the laser power exceeds a critical value. Again, Wang et al [25] found that there is an upper limit of the laser power for self-focusing in plasma beyond which the laser pulse is defocused due to the ponderomotive force.…”
Section: Introductionmentioning
confidence: 99%
“…It changes the electron density distribution and increases the dielectric constant therefore, leads to fast divergence of the laser beam. [23] Sprangle et al [24] investigated the relativistic self-focusing of short-pulse radiation beams in plasmas and reported that for self-focusing to occur, the laser power exceeds a critical value. Again, Wang et al [25] found that there is an upper limit of the laser power for self-focusing in plasma beyond which the laser pulse is defocused due to the ponderomotive force.…”
Section: Introductionmentioning
confidence: 99%